Dermatological Presentation of Strongyloides stercoralis Infection in Two Elderly Italian Inpatients - Gardini, Giulia; Froeschl, Guenter; Puzzi, Petra Rosa; Gambino, Silvia; Erne, Elke Maria (Pathogens (Basel), 2024)
Persistent infections caused by Strongyloides stercoralis are probably underestimated in the elderly Italian population. This nematode is unique among helminths: it can last asymptomatically in the host for decades and may present with a broad range of clinical pictures upon reactivation. Misdiagnosis often occurs even when the clinical picture is suggestive. If undetected, this parasitosis can lead to serious consequences when hyperinfection occurs. Herein, we report two peculiar clinical cases of complicated strongyloidiasis with multiple skin lesions. The aim of our report is to lead clinicians to familiarize themselves with skin patterns and clinical features that can suggest a possible underlying strongyloidiasis.